(untitled) (Research, Society and Development, 2023)
Oral antral communication can be associated with trauma/iatrogenesis, extraction of upper molars and various pathological changes, making it very common in dentistry, with the main reported symptoms being fever, pain and drainage of purulent secretion into the oral cavity. The objective of this study is to inform healthcare professionals about the importance of the Bichat ball as a potential surgical technique for closing oral antral contact. The analysis of articles was carried out in English and Portuguese (Brazil) indexed in the Pubmed, Scielo and Research Society and Development journal databases from 2014 to 2022, using the search strategy “Odontogenic sinusitis; Regenerative potential of the Bichat fat; Oroantral fistulas closure using Bichat’s fat; Bichectomy; Bucosinusal Communication”. Bichat Ball adipose tissue presents mesenchymal stem cells (with the presence of a stress-resistant multilineage subpopulation) with a strong proliferative potential of osteoblasts being capable of carrying out osteogenic differentiation, thus initiating the production of mineralized tissue. Conclusion: In view of this, the advantages of the Bichat cushion are: reduced disturbances and scars in the vestibule in relation to the flap sliding technique, being considered an easy and quick procedure, less pre-operative discomfort for the patient, low morbidity, possibility of combining it with other surgical techniques and possibility of adjustments after a week. The failure to use the oral fat body is mainly related to tension or excessive manipulation of the tissue resulting in its necrosis.